Three unpublished books by J. L. Fischer - Priban - Eduard Burget (†), Michal (Bohemica Olomucensia, 2025)
The deteriorating publishing conditions in the period that followed after the Soviet invasion of Czechoslovakia in August 1968 had far-reaching consequences. As early as the spring of 1969, publishing executives were altering editorial plans and removing politically problematic titles. In January 1970, a new censorship body was established at the Ministry of Culture of the Czechoslovak Republic, and the hitherto unclear censorship criteria began to take on concrete features. Several books that had already been printed but the Ministry forbade their distribution, they fell victim to this censorship. This harsh censorship practice also affected two books by the philosopher and sociologist Josef Ludvik Fischer, the first rector of the restored Palacky University in Olomouc. The Horizont publishing house in Prague published a revised an expanded reissue of his earlier book Glosses on the Czech Question, while the Profil publishing house in Ostrava published his study Socrates Illegendary. Neither of these books was allowed to be distributed. The study deals with the preparations and circumstances of their publication.
Keywords: J. L. Fischer; Palacky University; normalization after 1969; history of Czech publishing houses; censorship